Forward Modeling Simulations to Validate Changes in Electrical Resistivity Tomography Monitoring Data for a Slope with Complex Geology - Azadeh Hojat; Luigi Zanzi; Greta Tresoldi; Meng Heng Loke (Geosciences)
The electrical resistivity tomography (ERT) method has been increasingly integrated with hydrogeological risk mitigation strategies to monitor the internal conditions and the stability of natural and artificial slopes. In this paper, we discuss a case study in which numerical simulations were essential to validate the interpretation of the resistivity images obtained from an ERT monitoring system installed on a critical slope in Italy. An initial analysis of the monitoring data after rainfall events in the study site showed that the resistivity values were decreased only in the central zone along the ERT line, but they were increased in the two sides of the profile. Opposite behaviors were observed during the drying processes following the rainfall events. Core samples show complex geology at the study site, which might justify uneven responses of the different subsurface bodies to meteorological events. However, we decided to investigate the possible inversion artifacts resulting from the individual inversion of the tomographic sections. Forward modeling simulations on simplified time-lapse models of the study site were performed to explore this problem and to compare the individual and time-lapse inversions. Synthetic tests confirmed the nature of these unexpected behaviors and assessed the absolute necessity of a time-lapse approach for a correct inversion of monitoring data in the presence of a complex geological model such as the one of this case study. By applying the time-lapse inversion approach to the real data, the inversion artifact problem was substantially solved, arriving after the proper calibration of the inversion parameters, mainly the time-lapse damping factor and the spatial and temporal roughness constraints, to a reduction in the inversion artifacts to less than 5%.